PUBLIC PERCEPTION OF BILLBOARD ADVERTISING IN OSOGBO, NIGERIA: INSIGHTS FROM A QUALITATIVE STUDY - F. Y. Badmus-Olofintuyi, Christianah; Funmilayo Akinola, Grace; Ifeduba, Emmanuel (African Journal of Social and Behavioural Sciences, 2024)
Billboard advertising remains a pivotal component in marketing, utilising prominent locations, creative visuals, and emotional appeals to captivate audiences. This study explores public perception of billboard advertising in Osogbo, Osun State, examining its impact on organisational profit maximisation and associated challenges. Findings reveal that billboards are highly regarded for enhancing brand visibility and reaching diverse audiences, particularly non-digital populations. However, their effectiveness is undermined by challenges such as design clutter, oversaturation in certain areas, and limited viewer interaction time. Residents appreciate billboards for bridging traditional and digital media gaps, particularly in reaching non-digital audiences. However, issues such as fleeting attention spans and overemphasis on models rather than products diminish their impact. These insights underscore the need for strategic placements, simple messaging, and contextually relevant content to optimise billboard advertising outcomes. The study highlights the importance of strategic placement, concise messaging, and culturally relevant content to enhance billboard advertising outcomes. These insights contribute to the growing discourse on optimising advertising strategies in an increasingly competitive media landscape.